Islamic finance discourses - Sadique, Muhammad Abdurrahman (Managingdata, 2025)
‘Islamic Finance Discourses’ examines three contractual processes known as murabahah, tawarruq and ‘inah, which are varieties of sale discussed in Islamic legal literature that have gained prominence with the upsurge in Islamic banking in the recent decades. While murabahah comprises a single contract of sale, each of the remaining two refers to a process involving two fully independent sale contracts. In the original format discussed in Islamic law, murabahah is duly recognised as a valid classification of sale, whereas the validity and recognition of the other two have not been universal, especially ‘inah, which has come under juristic disapproval in many of its forms. These contracts, which are not among the important varieties of contracts in Islamic law, have drawn undue attention and prominence with their application as alternatives to interest-based loans in Islamic banking. The current work explores their essential nature and details as discussed in Islamic legal manuals, followed by a scrutiny of their adaptations in contemporary Islamic banking. It attempts to provide an analytical perspective of the areas discussed, and should prove to be of interest to academics and students of Islamic law and finance.